2003
DOI: 10.1074/jbc.m206262200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of α2,6-Sialyltransferase Cleavage by Alzheimer's β-Secretase (BACE1)

Abstract: BACE1 is a membrane-bound aspartic protease that cleaves the amyloid precursor protein (APP) at the ␤-secretase site, a critical step in the Alzheimer disease pathogenesis. We previously found that BACE1 also cleaved a membrane-bound sialyltransferase, ST6Gal I. By BACE1 overexpression in COS cells, the secretion of ST6Gal I markedly increased, and the amino terminus of the secreted ST6Gal I started at Glu 41 . Here we report that BACE1-Fc chimera protein cleaved the A-ST6Gal I fusion protein, or ST6Gal I-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 32 publications
3
72
0
1
Order By: Relevance
“…Similarly, we found that suppression of BACE1 expression by siRNA did not change the subcellular distribution of APP and presenilin-1, indicating that loss of BACE1 elicits no profound cellular defects. However, another BACE1 substrate (␣2,6-sialyltransferase) has been reported (34,35), and it will be important to determine whether alterations in this substrate have any effect on function. Despite this caveat, most data support the possibility that inhibition of BACE1 may not be toxic to animals or humans.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found that suppression of BACE1 expression by siRNA did not change the subcellular distribution of APP and presenilin-1, indicating that loss of BACE1 elicits no profound cellular defects. However, another BACE1 substrate (␣2,6-sialyltransferase) has been reported (34,35), and it will be important to determine whether alterations in this substrate have any effect on function. Despite this caveat, most data support the possibility that inhibition of BACE1 may not be toxic to animals or humans.…”
Section: Discussionmentioning
confidence: 99%
“…Both of BACE1-transgenic mice had elevated levels of plasma ST6Gal I as compared with the control mice (Fig. 2, lower panel) 43 at the amino terminus, and then the three terminal amino acids, Gln-AlaLys, were trimmed by a luminal aminopeptidase(s) to produce the E41 form that is secreted from the cells (26).…”
Section: Plasma St6gal I Levels Were Decreased In Bace1-deficientmentioning
confidence: 99%
“…The majority of serum ST6Gal I is secreted from the liver (21,22), and secretion is enhanced during acute-phase hepatic reactions (23,24). We previously found that BACE1 is involved in the cleavage and secretion of ST6Gal I, at least in cultured cells (25,26), leading to an assumption that BACE1 cleaves ST6Gal I in the liver and triggers its secretion into plasma.…”
Section: A Characteristic Feature Of Alzheimer Disease (Ad)mentioning
confidence: 99%
“…The cytosolic tail/transmembrane domain/stem region of human ST6Gal I is probably implicated in subcellular traffic through functional homodimerization and/or interactions with other proteins, such as COP-I coated vesicle anterograde traffic of GT or COG (103,(107)(108)(109)(110)(111) or Golgi retention (112)(113)(114) and in the modulation of its enzymatic activity through substrate recognition (61). It has also been shown that the cytosolic tail/transmembrane domain/stem region impacts mammalian ST6Gal I secretion via BACE-1 aminopeptidase activity in Alzheimer disease (115)(116)(117)(118). Altogether, our data on the molecular cloning of lower vertebrate st6gal1 genes and their molecular evo-lution raise the question of the evolution of vertebrate ST6Gal I with regard to their subcellular localization, interaction with other glycosyltransferases, and activity in vivo.…”
Section: Discussionmentioning
confidence: 99%